Reductions in Intestinal Taurine-Conjugated Bile Acids and Short-Chain Fatty Acid-Producing Bacteria Might be Novel Mechanisms of Type 2 Diabetes Mellitus in Otsuka Long-Evans Tokushima Fatty Rats - Yang, Xiaoyun; Jiang, Wenhui; Cheng, Jingli; Hao, Jintong; Han, Fei; Zhang, Yi; Xu, Jie; Shan, Chunyan; Wang, Jingyu; Yang, Yanhui; Yang, Juhong; Chang, Baocheng (Experimental and Clinical Endocrinology & Diabetes, 2021)
Background The pathogenesis of spontaneously diabetic Otsuka Long-Evans Tokushima Fatty (OLETF) rats, among the best models for human type 2 diabetes mellitus (T2DM), remains poorly defined. Therefore, we investigated the dynamic changes in taurine-conjugated bile acids (T-BAs) and intestinal microbiota during T2DM development in OLETF rats.Methods OLETF rats and corresponding diabetes-resistant Long Evans Tokushima Otsuka (LETO) rats were fed a normal baseline diet. The progress of T2DM was divided into four phases, including normal glycemia-normal insulinemia (baseline), normal glycemia-hyperinsulinemia, impaired glucose tolerance, and DM. Body weight, liver function, blood lipids, fasting plasma glucose, fasting plasma insulin, fasting plasma glucagon-like peptide (GLP)-1 and GLP-2, serum and fecal T-BAs, and gut microbiota were analyzed during the entire course of T2DM development.Results There were reductions in fecal T-BAs and short-chain fatty acids (SCFAs)-producing bacteria including Phascolarctobacterium and Lactobacillus in OLETF rats compared with those in LETO rats at baseline, and low levels of fecal T-BAs and SCFAs-producing bacteria were maintained throughout the whole course of the development of T2DM among OLETF rats compared with those in corresponding age-matched LETO rats. Fecal taurine-conjugated chenodeoxycholic acid correlated positively with Phascolarctobacterium. Fecal taurine-conjugated deoxycholic acid correlated positively with Lactobacillus and fasting plasma GLP-1 and inversely with fasting plasma glucose.Conclusion The fecal BAs profiles and microbiota structure among OLETF rats were different from those of LETO rats during the entire course of T2DM development, indicating that reductions in intestinal T-BAs and specific SCFA-producing bacteria may be potential mechanisms of T2DM in OLETF rats.
Keywords: Short-chain fatty acid; Taurine-conjugated bile acids; Bacteria; OLETF Rats; Type 2 diabetes mellitus